A global assessment of closed forests, deforestation and malaria risk - GUERRA, C. A. (2006)
Global environmental change is expected to affect profoundly the transmission of the parasites that cause human malaria. Amongst the anthropogenic drivers of change, deforestation is arguably the most conspicuous, and its rate is projected to increase in the coming decades. The canonical epidemiological understanding is that deforestation increases malaria risk in Africa and the Americas and diminishes it in South–east Asia. Partial support for this position is provided here, through a systematic review of the published literature on deforestation, malaria and the relevant vector bionomics. By using recently updated boundaries for the spatial limits of malaria and remotely-sensed estimates of tree cover, it has been possible to determine the population at risk of malaria in closed forest, at least for those malaria-endemic countries that lie within the main blocks of tropical forest. Closed forests within areas of malaria risk cover approximately 1.5 million km(2) in the Amazon region, 1.4 million km(2) in Central Africa, 1.2 million km(2) in the Western Pacific, and 0.7 million km(2) in South–east Asia. The corresponding human populations at risk of malaria within these forests total 11.7 million, 18.7 million, 35.1 million and 70.1 million, respectively. By coupling these numbers with the country-specific rates of deforestation, it has been possible to rank malaria-endemic countries according to their potential for change in the population at risk of malaria, as the result of deforestation. The on-going research aimed at evaluating these relationships more quantitatively, through the Malaria Atlas Project (MAP), is highlighted.